2021
DOI: 10.1007/s00453-021-00812-z
|View full text |Cite
|
Sign up to set email alerts
|

Finding and Counting Permutations via CSPs

Abstract: Permutation patterns and pattern avoidance have been intensively studied in combinatorics and computer science, going back at least to the seminal work of Knuth on stack-sorting (1968). Perhaps the most natural algorithmic question in this area is deciding whether a given permutation of length n contains a given pattern of length k. In this work we give two new algorithms for this well-studied problem, one whose running time is $$n^{k/4 + o(k)}$$ n … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Theorem 6 (Berendsohn et al [6]). Given a length-k permutation π and length-n permutation σ, the number of occurrences of π in σ can be counted in time n k/3+o(k) .…”
Section: Finding and Counting Permutation Patternsmentioning
confidence: 98%
See 4 more Smart Citations
“…Theorem 6 (Berendsohn et al [6]). Given a length-k permutation π and length-n permutation σ, the number of occurrences of π in σ can be counted in time n k/3+o(k) .…”
Section: Finding and Counting Permutation Patternsmentioning
confidence: 98%
“…The problem is often called Permutation Pattern Matching and is known to be NP-hard [16], but of course can be solved in time O(n k ) by brute force. Albert et al [3] improved this to O(n 2/3k+1 ) time, Ahal and Rabinovich [2] further improved it to n 0.47k+o(k) time, and Berendsohn et al [6] gave an n 0.25k+o(k) time algorithm. Guillemot and Marx [49] showed that Permutation Pattern Matching can be solved in time 2 O(k 2 log k) • n, that is, it is fixed-parameter tractable (FPT) parameterized by the length of π.…”
Section: Finding and Counting Permutation Patternsmentioning
confidence: 99%
See 3 more Smart Citations